Mouse and Drosophila genes encoding the major heat shock protein (hsp70) are highly conserved. - Lowe, D G (1983)
We used a cloned Drosophila melanogaster hsp70 gene to hybrid-select heat shock-induced mouse mRNA and showed that this mRNA encodes the major mouse heat shock protein. This result suggests that the sequence of the hsp70 gene(s) is highly conserved.